Positioning environmental education in the South African classroom: the case of the Grade 11 Geography Curriculum - Ndaba, Thobile; Fru, Raymond (Penerbit Universiti Kebangsaan Malaysia, 2024)
The teaching of environmental education in the South African classroom is challenging. Although the Curriculum and Assessment Policy Statement (CAPS) provides for the integration of environmental education across subjects and grades, there are contextual limitations that educators (in the case of this study geography educators) face when having to teach environmental education. This problem is further compounded by limited research on the contextual challenges faced by geography educators when teaching environmental education and environmental awareness principles. This study investigates how geography educators conceptualise and teach environmental education and environmental awareness principles in the geography grade 11 classroom. The findings indicate that educators’ conceptualisation of environmental education, and how they teach it varies according to the setting that they are in. They expressed challenges faced due to inadequate resources to teach environmental education, as well as the inability to assess learners’ pro-environmental behaviour due to it not being allocated in the curriculum.